Preoperative tumor marking with indocyanine green prior of robotic colorectal resections - Konstantinidis, Michael K.; Ioannidis, Argyrios; Vasiliou, Pantelis; Arkadopoulos, Nikolaos; Papanikolaou, Ioannis S.; Chand, Manish; Pampiglione, Tom; Karagiannis, Dimitrios; Konstantinidis, Konstantinos (Frontiers in Surgery, 2022)
This prospective case-series study aimed to assess the usefulness of preoperative colonoscopic marking of colorectal tumors using Indocyanine Green (ICG) fluorescence in patients that underwent robotic surgical colorectal resections. Consecutive patients that were eligible for colorectal resection with intent to cure in a single hospital (Athens Medical Center), from February 2022 to June 2022, were included. ICG solution was injected into the submucosal layer at 2 opposite sites (180 degrees apart) distal to the tumor, without submucosal elevation. Identification of the tumor marking was then performed after switching to near-infared (NIR) fluorescence mode. During the robotic procedure, qualitative evaluation of fluorescence was performed by the surgical team (primary surgeon, first assistant, second assistant, research fellow). All 10 patients underwent robotic surgical approach and operations included right-sided colectomy (n = 1), left-sided colectomy (n=6) and low anterior resection (n = 3). Visualisation of this dye with near-infrared light was very clear with bright intensity in all patients when the marking was performed one day prior of surgery. Preoperative tumor marking with ICG was identified intraoperatively in all cases and the techinque was easily reproducible.